Serum thioredoxin and lactoferrin in rheumatoid arthritis and their association with rheumatoid factor - Delcheva Ginka; Stefanova Katya; Stankova Teodora; Maneva Ana (Journal of Medical Biochemistry)
Background: Thioredoxin (Trx) and lactoferrin (Lf) are multifunctional proteins that are part of the body's antioxidant defence and counteract oxidative tissue damage. Our study aims to investigate Trx and LF levels in the serum of rheumatoid arthritis (RA) patients and establish the association of these proteins with the rheumatoid factor (RF) and other disease markers. Methods: The study included 114 patients with RA and 42 healthy subjects. Serum concentrations of Trx 1, LF, RF, anti-cyclic citrullinated peptide (anti-CCP) antibodies, Creactive protein (CRP), and IL-6 were determined using commercially available ELISA kits. Results: Serum thioredoxin 1 levels in RA were significantly higher compared to the control group, 36.4 (29.6-40.2), ng/mL versus 19.0 (16.3-26.8), ng/mL, p<0.0001. Serum lactoferrin levels were elevated in RA compared to the control group. However, the difference was not statistically significant, 579.6 (312.8-947.5) ng/mL versus 519.0 (262.5-928.0) ng/mL. We found substantial negative Trx 1 and LF correlations with rheumatoid factor in RA (r=-0.254, p=0.05 and r=-0.238, p=0.014, respectively). The correlations of thioredoxin and lactoferrin with other disease markers, such as anti-CCP antibodies, DAS28, erythrocyte sedimentation rate (ESR), CRP, and IL6 were not statistically significant. A strong positive correlation between Trx 1 and LF was observed in the study group of RA patients (r=0.519, p<0.0001) but not in the control group. Conclusions: Thioredoxin and lactoferrin were associated with rheumatoid factor but not with anti-CCP antibodies and systemic disease activity; therefore, the two proteins may serve as new biomarkers for assessing pathological changes and monitoring disease severity and progression in RA.